2018
DOI: 10.11591/ijpeds.v9.i4.pp1851-1865
|View full text |Cite
|
Sign up to set email alerts
|

Control Methods on Three-phase Power Converters in Photovoltaic Systems

Abstract: <span lang="EN-US">In this paper, a three-phase load connected to a NPC three-level inverter is presented. To generate gate signals for the multilevel inverter, two commands are developed and compared: the phase disposition pulse width modulation (PDPWM) and the space vector pulse width modulation (SVPWM). DC supply is provided by photovoltaic cells. Boost converter controls the power transfer from photovoltaic generator. Due to nonlinear I-V characteristics of photovoltaic cells, a maximum power point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It serves well in a low-temperature water-heating system. Many other papers [21]- [26] studied the back-surface cooling numerically and experimentally and found that there is a good agreement between the numerical results and the experimental measurements performed for the climate of Dhahran, Saudi Arabia. Back surface cooling technique dropped significantly the module temperature to about 20%, which led to an increase in the electrical efficiency of the PV panel by 9%.…”
Section: Design Of the Systemmentioning
confidence: 71%
“…It serves well in a low-temperature water-heating system. Many other papers [21]- [26] studied the back-surface cooling numerically and experimentally and found that there is a good agreement between the numerical results and the experimental measurements performed for the climate of Dhahran, Saudi Arabia. Back surface cooling technique dropped significantly the module temperature to about 20%, which led to an increase in the electrical efficiency of the PV panel by 9%.…”
Section: Design Of the Systemmentioning
confidence: 71%
“…Nonetheless, high power utilization required sinusoidal waveforms with low distorted characteristics. This causes four modes and six modes switching inverter not recommended due to remarkably low-quality waveform due to the presence of harmonic distortion [3], [4]. To apprehend this demerit, the multi-level inverter (MLI) concept which produces a multi-stepped or ladder waveform was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…All types of MLI discussed so far requires a control signal for operating the power electronics components present in the circuit. There are various control techniques available to effectively operate the power electronics components in order to achieve quality staircase output waveform [18][19][20][21][22][23][24]. In recent years Pulse Width Modulation (PWM) based control techniques are widely used due to various reasons like less switching losses and less stress on power electronics components.…”
Section: Introductionmentioning
confidence: 99%